Minangkabau peace literature in West Sumatra: A critical discourse analysis - Wening Udasmoro (Faculty of Social and Political Science, Universitas Airlangga, 2019)
This research paper, focusing on the oral literature regarding peace in Minangkabau, West Sumatra, does not simply examine the meaning of oral literature, but also attempts to connect such literature with the social practices of its consumers. This has been carried out in an attempt to understand how, if peace literature is still a part of Minangkabau society, conflict and other acts of violence in the society can still occur. Three important questions must be answered: 1) How are works of oral literature regarding peace produced, consumed, and reproduced among the Minangkabau in Padang, West Sumatra? 2) Who is most involved in reproducing peace literature? 3) How is oral literature regarding peace related to social practices of peace? Critical discourse analysis can be a useful method for literary research. This can be attributed to the fact that works of literature are not simply fictional, but also social, meaning that they play an important role in bridging fact and fiction. The intent of this paper is to examine the connection between oral literature regarding peace and its discursive context through a strict investigation of the three layers of critical discourse analysis: linguistic practice, discursive practice, and social practice. The findings of this paper are that every generation creates their own definition of peace literature. Surau, family, schools, and media are the institutions that play important roles in producing peace literature. Young generations from different age categories consume and reproduce such literature based on their understanding of the discourses, despite the fact that they do not always follow the discourses in their social practices.